Trading in human organs - Jalil Ismael Al-Rubaie, Dunya (International Journal of Psychosocial Rehabilitation, 2020)
Human traffickers are a global problem that is spreading illegally and is increasing in many societies; although it is sometimes a refuge to save the lives of many people in rich countries, it leads to the alarming spread of crime and the end of the lives of a large proportion of people in other countries, especially countries (Moroccan, 2012, p. 5) The phenomenon of human trafficking has become an international phenomenon as it is not limited to one country but extends to many countries as a result of being a form of organized crime but varies according to its forms and patterns from one country to another according to the concept of human trafficking in its legislation and its respect for human rights. The international community has recently witnessed an escalation of the phenomenon of trafficking, particularly with the growing hotbeds of armed conflicts, both national and international, the presence of many regions of the world suffering from internal unrest, political instability and deteriorating economic conditions in some countries, particularly For the third world, which provides organized crime gangs with living conditions that have facilitated the existence of renewed resources from victims in order to make huge sums of money from their exploitation. Human trafficking is the third largest trade in the world after drugs and arms trafficking, as women, children, and young people are the most important victims, as traders are made from poor countries as a source of victims and poor countries are popular markets for their trade (Yunus 2005, p. 6).